Physicochemical and Sensory Characterization of Gnocchi and the Effects of Novel Reformulation on in Vitro Digestibility - Liu, Tingting (Auckland University of Technology, 2014)
Conventional gnocchi are small Italian dumplings made from potatoes, flour, and sometimes eggs. They contain a large amount of carbohydrate but are a poor source of protein. In this study, we sought to develop a gnocchi-type food with added nutritional ingredients: navy bean and beef. Our hypothesis is that addition of meat and navy bean will improve the nutritional, physicochemical and sensory properties of the reformulated gnocchi. In this study, gnocchi formulations with added meat and navy bean ingredients at concentrations between 10 - 40% (w/w) were developed. All samples were evaluated for their physicochemical, nutritional and sensory attributes. In addition, Modified in vitro Stomach Stir Tank (MISST) was used to analyse the changes caused by addition of the new ingredients on the digestibility of the developed gnocchi. Samples containing 30 and 40% meat had significantly higher fat and protein content. Addition of meat significantly increased the redness and decreased the lightness of both raw and cooked gnocchi sample according to the L*, a*, b* colour system. The combination of navy bean and meat incorporated into gnocchi formulation significantly increased hardness, springiness and chewiness of most cooked gnocchi samples. Samples with similar texture to the commercial gnocchi sample and a control sample were then subjected to consumer sensory testing and projective mapping. There were no significant differences in overall liking and liking of other attributes (odour, taste, texture and flavour). The product and attribute maps obtained from projective mapping separated the control sample from the other samples due to its soft texture. Samples 40M , 30M and 20M10N were associated with a hard texture, while 20M and 10M were associated with chewy, and a neither hard nor soft texture. Samples 40M, 30M, 10M, 10M30N, and 20M10N were also tested for their in vitro digestibility. The pH increased when the food bolus entered the stomach compartment, and then decreased after the feeding period ceased. As the hydrolysis of starch ended in the stomach in our study, the hydrolysis ratio of digested starch vs. total starch were measured. The initial hydrolysis ratio of the gnocchi samples ranged from 30% to 41%. The hydrolysis ratio decreased after 50 minutes of in vitro digestion. The sample with the highest meat content (40M) had the highest concentration and mass of total water soluble protein at all times, followed by 30M. Overall, the results showed that the incorporation of meat and navy bean changed the nutritional, physicochemical and the in vitro digestibility properties of gnocchi. The outcome of the present study will have greater impact on extending the use of meat to develop healthier food products and aligns with the AgResearch programme “Red Meat Combifoods: End to end management of protein nutrition” supported by the Crown Research Institute Core Fund of AgResearch Ltd. 1 Samples are expressed as percentage meat (M) and navy bean (N) content. For example, 20M10N refers to the gnocchi sample containing 20% meat and 10% navy bean.
Keywords: Gnocchi; Reformulation; Navy bean; In vitro digestibility; Meat; Projective mapping; TPA; Nutritional composition